The global effect of the current technological revolution 4th industrial revolution and industry 4.0 in action (GEON Journal (Management, Organizations and Business), 2020)
The motivation to investigate the 4th Industrial Revolution is that it is already actively present in many developed countries and to a much lesser extent in Latin American countries.The Latin American scientific community has not focused on investigating in depth the changes that the 4th Industrial Revolution is introducing require, given the low support of university institutions. This will generate important benefits to the scientific community since it exposes the different technologies that make up this revolution for its profound application, teaching and interrelation.This work will be divided into three chapters. The first considers an analysis of the previous revolutions up to the fourth industrial revolution, describing technological trends. The second point out the elements inherent in Industry 4.0 and the changes in the talent requirement. The third chapter analyzes the relationship between the fourth industrial revolution and the area of ​​business human resources.As relevant results, it should be noted that technology is driving disruptive changes and innovations that are modifying the current reality. On the other hand, it should be noted that the human resource management of organizations is not adapting to the new demands and requirements of talent to be incorporated into Latin American organizations.The practical implications of the research for this paper indicate that not incorporating into these new technological processes of Industry 4.0, can imply poverty and significant disadvantages for Latin countries.
Keywords: Industrial revolution; Industry 4.0; Technology; Social Impact; Talent